Transcriptomic and metabolomic integration as a resource in grapevine to study fruit metabolite quality traits - Savoi, Stefania; Santiago, Antonio; Orduña, Luis; Matus, José Tomás (Frontiers in Plant Science, 2022)
Transcriptomics and metabolomics are methodologies being increasingly chosen to perform molecular studies in grapevine. Currently, the integration of these approaches has become of utmost relevance when studying key plant physiological and metabolic processes. The results from these analyses can undoubtedly be incorporated in breeding programs whereby genes associated with better fruit quality or with stress resistance can be used as selection markers in crop improvement programs. Despite the amount of data being generated, integrative transcriptome/metabolome meta-analyses have not yet been fully accomplished in this species, mainly due to particular specificities of metabolomic studies, such as differences in data acquisition, unappropriated and unstandardized metadata, or simply no deposition of data in public repositories. These meta-analyses require a high computational capacity for data mining a priori, but they also need appropriate tools to explore and visualize the integrated results. This perspective article explores the universe of omics studies conducted in V. vinifera, focusing on fruit-transcriptome and metabolome analyses as leading approaches to understand berry physiology, secondary metabolism, and quality. Moreover, we show how omics data can be integrated in a simple format and offered to the research community as a web resource, giving the chance to inspect potential gene-to-gene and gene-to-metabolite relationships that can later be tested in hypothesis-driven research. In the frame of the activities promoted by the COST Action INTEGRAPE, we present the first grapevine transcriptomic and metabolomic integrated database developed within the Vitis Visualization platform. This tool also enables the user to conduct and explore meta-analyses utilizing different experiments.